(untitled) (International Journal of Food and Nutritional Sciences, 2022)
On 1st January, 1995, the WTO brought an agreement which has the force of law across the nations, which is the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) for protection of Intellectual Property Rights. The world was not at the same level when such agreements were brought to force. There were differences on the social, economic and cultural front. There were therefore conflicts in implementing such laws. United States has been very active in obtaining intellectual property protection for its agricultural biotechnology during TRIPS negotiations. This strong protection for gene seeds has increased concerns for other countries’ farmers and non-governmental organizations. The only argument these countries have is the concept of ‘food sovereignty’. This implies that "the right of each nation to maintain and develop its own capacity to produce its basic foods respecting cultural and productive diversity.” The content of this rights is controversial and unclear as to the basic concept of human rights. The present paper is inclined towards applying human right approach to this protection of Genetically Modified Crops.